Transference patterns and working alliance during the early phase of psychodynamic psychotherapy - Samardžić, Ljiljana; Nikolić, Gordana (Vojnosanitetski pregled, 2015)
Background/Aim. Working alliance, as a collaborative part of the therapeutic relationship has been proven to be one of the most powerful therapeutic factors in psychotherapy in general, regardless many technical differences between numerous psychotherapeutic modalities. On the other hand, transference is the basic concept of psychodynamic psychotherapy, and, according to the psychoanalytic theory and practice, it forms a major part of the therapeutic relationship. The aim of our paper was to determine the differences between the groups of patients with low, middle, and high working alliance scores and the dropout group in transference patterns, socio-demographic and clinical parameters, during the early phase of psychodynamic psychotherapy. Methods. Our sample consisted of 61 non-psychotic patients, randomly selected by the method of consecutive admissions and treated with psychoanalytic psychotherapy in the outpatient clinical setting. The patients were prospectively followed during 5 initial sessions of the therapeutic process. The working alliance inventory and Core conflictual relationship theme method were used for the estimation of working alliance and transference patterns, respectively. According to the Working Alliance Inventory scores, four groups of patients were formed and than compared.  Results. Our results show a significant difference between the groups of patients with low, middle, and high working alliance inventory scores and the dropout group on the variable – transference patterns in the therapeutic relationship. Conclusion. Disharmonious transference patterns are more frequent in patients who form poor quality working alliance in the early phase of psychotherapy, or early dropout psychotherapy. It is of great importance to recognize transference patterns of a patient at the beginning of the psychotherapeutic process, because of their potentially harmful influence on the quality of working alliance.
Keywords: psychotherapy; young adult; physician-patient relations; transference (psychology)